Conocimientos y prácticas sobre enfermedades crónicas no transmisibles y su relación con estilos de vida en estudiantes del Colegio Adolfo Valarezo - Granda Paredes, Yuli Estefania (2019)
According to the Organizacion Mundial de la Salud (OMS), chronic non-transmissible diseases are long-term disorders with a generally slow progression, which represent the main cause of morbidity and mortality in the world. This study is descriptive and cross-sectional, it was conducted at the Adolfo Valarezo high school in the city of Loja, 2018-2019 school year. The objective was to determine knowledge and practices on chronic non-transmissible diseases and their relationship with students' lifestyles; the sample was represented by 233 students in order to obtain the information. A structured survey was used as an instrument which allowed to determine that in 65% of the students do not know the definition, in relation to symptoms 85 to 96% do not know and only 46% identify diabetes mellitus as a chronic non-transmissible disease, In terms of the causes, more than 70% know them; according to the lifestyles practiced by the students, it was determined that 77% of their diet is inadequate; on the other hand, 81% engage in physical activity and 75-86% do not consume alcohol and cigarette. It is concluded that the diet lifestyle is not adequate and could in the future have an impact on their health and lead to chronic non-transmissible diseases. Key words: Pathologies, Morbidity, Mortality, High school teenagers, Healthy habits.